The impact of age on the Na:K ratio: observations from a general canine population - Zemko, Polina; Bonsembiante, Federico; Canevelli, Marco; Banzato, Tommaso (Frontiers in Veterinary Science, 2025)
IntroductionThe sodium-to-potassium (Na:K) ratio is commonly used as a screening criterion for hyponatremic and/or hyperkalemic hypoadrenocorticism (HA), a serious endocrine disorder in dogs characterized by non-specific clinical signs and variable laboratory findings. A Na:K ratio below 27 typically prompts further investigation through adrenal function tests. However, previous studies suggest that serum K levels may increase with age, even in otherwise healthy dogs. The objective of this study is to evaluate the influence of age on the Na:K ratio, in order to determine whether age-related changes could impact the reliability of this ratio as a screening tool in adult and senior dogs.Materials and methodsWe analyzed biochemical and hematological data from 208 dogs, aged 5–16 years, enrolled in a longitudinal research project of general canine population. The data included their medical history before the control visit and during the 12-month follow-up period.ResultsThe prevalence of dogs with a Na:K ratio ≤ 27 was found to be 2.4 ± 2.7% in dogs under 10 years and 12.8±7.0% in those over 10 years. None of the dogs with Na:K ratio ≤ 27 had clinical suspicion of HA, either at the time of initial evaluation or during the 6-months follow-up period. Serum K levels showed a modest but statistically significant age-related increase of 0.22 ± 0.05 mEq/L every 5 years, while Na levels remained stable. As a result, the Na:K ratio declined by 1.5 ± 0.3 points every 5 years. Serum K was moderately correlated with the plateletcrit (PCT) (r = 0.39, p-value < 0.00001) and PCT was found to increase by 5.9% ± 1.6% every 5 years. It was estimated that each 10% increase in PCT corresponded to 0.142 ± 0.027 mEq/L rise in serum K.DiscussionThe prevalence of dogs with a Na:K ratio ≤ 27 increases with age, reducing the specificity of this threshold for diagnosing HA in older dogs—particularly when Na levels are within the normal range. This decline is due largely, though not exclusively, to age-related increases in PCT, as platelets release K during clotting.